"Formalizing rights: The case for linking legal rights to noncitizen statuses in Jordan". (12th October 2021) - Frost, Lillian
Abstract: How can Jordan's experiences hosting Palestinian refugees inform policymaking toward Syrian refugees? As the 10‐year anniversary of the Syrian uprisings approaches, Syrian refugees remain displaced with limited opportunities for repatriation, resettlement, or naturalization. Although there are many important differences between Syrian and Palestinian refugees—particularly Syrians' right to a sovereign state's nationality—there are increasing similarities between these two protracted refugee groups. One of the most critical among these similarities is holding ambiguous membership statuses in Jordan, where groups hold more rights than other non‐Jordanians but fewer rights than Jordanian citizens. The experiences of noncitizen Palestinian refugees, such as those who fled to Jordan from the Gaza Strip after the 1967 war, highlight the destructive precarities that accompany an absence of legal rights, including insecure access to work, education, and healthcare. These experiences suggest that securing some Syrian rights in law can help mitigate the precarity of sustained refugee status. Further, Jordan has expressed a willingness to provide legal rights to some noncitizen groups, including investors and the children of Jordanian women and non‐Jordanian men. Overall, formalizing critical, less politicized rights in law is one tangible way to improve the daily lives of Syrian, as well as other, protracted refugees.